Seed‐dispersal networks are more specialized in the Neotropics than in the Afrotropics - Dugger, Phillip James (2019)
Fil: Dugger, Phillip James. Universidad de Antioch Nueva Inglaterra. Departamento de Estudios Ambientales; Estados Unidos.